Post-natal care: a vital chance to save mothers and infants! Exploring barriers and factors associated with it: a mixed study - Dibaba Degefa, Bekem; Feyisa, Gizu Tola; Dinagde, Dagne Deresa; Kitil, Gemeda Wakgari; Walle, Agmasie Damtew (Frontiers in Global Women's Health, 2023)
The most effective maternal health intervention for enhancing mother and baby survival is postnatal care, yet it is also the most neglected services in Ethiopia. Less is known about postnatal care, despite earlier studies concentrating on pregnancy and delivery service consumption. Postnatal care is the subject of few national and local area research. Therefore this study aims to evaluate postnatal care utilization; barriers and associated characteristics among women in Ilubabor zone and buno bedele zone. A mixed-methods study involving women who visited immunization clinics was conducted in southwest Ethiopia. For the quantitative part, a cross-sectional survey was conducted between June 12 and July 12, 2022. The data collected through interviews was analysed using SPSS version 26. An adjusted odds ratio (AOR) with a 95% Confidence Interval (CI) and p-value was constructed to evaluate the associations between postnatal care service utilization and explanatory variables. The usage of postnatal care services was determined to be significantly correlated with explanatory variables in multivariable logistic regression with a p-value less than 0.05. This qualitative study used two focused group discussions and two in-depth interviews to gather data from purposively selected mothers, and thematic analysis was used to analyse the data. A total of 422 participants with a 100% response rate were included in the analysis. 234 (55.5%) of these underwent postnatal checks. In the quantitative section, postnatal care counseling and appointment setting, counseling on danger signs, and prior postnatal care utilization all demonstrated a statistically significant association with the use of postnatal care services (AOR = 3.6, 95% CI (1.47-7.23)), [AOR = 2, 95% CI (1.05-3.64)], and [AOR = 3, 95% CI (1.36-58), respectively). At the qualitative level, it was determined that the themes of knowledge and access were obstacles to the use of postpartum care services. Generally this study revealed that Ilubabor zone and Buno Bedele zone has a poor total PNC service utilization rate. Furthermore Ignorance, conventional wisdom, religious activity, distances, environmental exposure and waiting time were identified as barriers to post-natal care service utilization. To optimize the service, all parties involved should work on these factors.